Efektivitas Penggunaan Metode Oral Drill Untuk Latihan Kemampuan Berbicara Bahasa Jepang Di Kelas Dasar - Nur Saadah Fitri Asih (Lingua Cultura, 2007)
Article content a research result about effectiveness of oral drill method to practice speaking ability of Japanese in elementary class.  This is an experiment research to Japanese course’s student in elementary class in BLCI (British Language Course of Indonesia) Bandung at 2006 year.  Experiment research is according to the condition of learning Japanese to the experiment class with oral drill method, in the other hand to the experiment class in using another method which is eklektik method that combine translating method and grammar method. Research data was got from result of the final test from the experiment class an control class.  From the process result and analize data can be know that the average score of the student’s speaking ability in experiment class is bigger than the average score of the student’s speaking ability in control class.